Overexpression of the C4 protein of tomato yellow leaf curl Sardinia virus increases tomato resistance to powdery mildew - D’Errico, Chiara; Forgia, Marco; Pisani, Marco; Pavan, Stefano; Noris, Emanuela; Matić, Slavica (Frontiers in Plant Science, 2023)
Powdery mildew (PM) is one of the most important diseases of greenhouse and field-grown tomatoes. Viruses can intervene beneficially on plant performance in coping with biotic and abiotic stresses. Tomato yellow leaf curl Sardinia virus (TYLCSV) has been reported recently to induce tolerance against drought stress in tomato, and its C4 protein acts as the main causal factor of tolerance. However, its role in response to biotic stresses is still unknown. In this study, transgenic tomato plants carrying the TYLCSV C4 protein were exposed to biotic stress following the inoculation with Oidium neolycopersici, the causal agent of tomato PM. Phytopathological, anatomic, molecular and physiological parameters were evaluated in this plant pathosystem. Heterologous TYLCSV C4 expression increased the tolerance of transgenic tomato plants to PM, not only reducing symptom occurrence, but also counteracting conidia adhesion and secondary hyphae elongation. Pathogenesis-related gene expression and salicylic acid production were found higher in tomato transgenic plants able to cope with PM compared to infected wild-type tomato plants. Our study contributes to unravelling the mechanism leading to PM tolerance in TYLCSV C4-expressing tomato plants. In a larger context, the findings of TYLCSV C4 as a novel PM defence inducer could have important implications in deepening the mechanisms regulating the management of this kind of protein to both biotic and abiotic stresses.